DIAGNOSA PENYAKIT DEMAM BERDARAH DENGUE DENGAN PENDEKATAN FUZZY - Mariyati Mariyati; Muhammad Ahsar Karim; Oni Soesanto (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2013)
Dengue Hemorrhagic Fever (DHF) is still one of the major public health problems in Indonesia. This study aims to diagnose dengue fever with fuzzy approach. Fuzzy approach used in this research is fuzzy inference system. The process of this fuzzy inference system consists of three main stages of fuzzification, evaluation of rules and inference, and defuzzification. The inference method used is the Tsukamoto Method. The results stated that the basic rules of fuzzy in diagnosing Dengue Hemorrhagic Fever is formed based on information obtained from the results of consultation with two doctors regarding the diagnosis of DHF and WHO 2009. The basic rules of fuzzy formed that is as many as 483 rules. The results showed that the level of fitting diagnosis of febrile illness bleeding dengue based on the results of fuzzy approach with the diagnosis of the doctors by 77%.